An Ancient Baboon Genome Demonstrates Long-Term Population Continuity in Southern Africa. (5th February 2020) - Mathieson, Iain; Abascal, Federico; Vinner, Lasse; Skoglund, Pontus; Pomilla, Cristina; Mitchell, Peter; Arthur, Charles; Gurdasani, Deepti; Willerslev, Eske; Sandhu, Manj S; Dewar, Genevieve
Abstract: Baboons are one of the most abundant large nonhuman primates and are widely studied in biomedical, behavioral, and anthropological research. Despite this, our knowledge of their evolutionary and demographic history remains incomplete. Here, we report a 0.9-fold coverage genome sequence from a 5800-year-old baboon from the site of Ha Makotoko in Lesotho. The ancient baboon is closely related to present-day Papio ursinus individuals from southern Africa—indicating a high degree of continuity in the southern African baboon population. This level of population continuity is rare in recent human populations but may provide a good model for the evolution of Homo and other large primates over similar timespans in structured populations throughout Africa.